Riesgo psicosocial emocional-conductual en adolescentes del Colegio Juan Montalvo sección nocturna de marzo a agosto del 2010 - Castro Daul, Jorge G. (2011)
Psychosocial risks are hazards that can lead a person to adverse events or actions, at times (stages) of development induced by deficiencies or personal problems we performed descriptive prospective study, adolescents who attend the Juan Montalvo High School night section, a sample of 173 students.